Privatization, public service and digitization. The case of 7 TV - Rodríguez Gómez, Eduardo Fco. (2022)
This research contributes to the study of the privatization processes experienced by public audiovisual media in a context of digital convergence. We conducted a case study of 7 TV, which was carried out by means of document analysis complemented with in-depth interviews. The goal is to analyze a regional public television, examining whether the complete privatization of this public service has promoted its digitalization, improving its transparency and accountability, and favoring citizens’ participation in decision-making. The main finding is that, despite being aware of the changes that must be undertaken to face the imminent transformation of the audiovisual sector, 7 TV is in an incipient phase of this process, anchored to a conservative production and distribution system that produces modest initiatives and where citizens’ participation is highly limited.